Recovery of ethanol from alcoholic beverages seized by the Federal Revenue Service in the triple border area between Brazil, Paraguay and Argentina - Furtado, Andréia Cristina; Ferreira, Wagner (Latin American Journal of Energy Research, 2025)
Ethanol is an organic substance with a saturated carbon chain, whose functional group is the hydroxyl group. The raw materials used in alcohol production are mainly of agricultural origin, and in Brazil, the main one is sugarcane, from which hydrated ethanol, anhydrous ethanol, and fine ethanol are obtained, used in various industrial segments or as fuel. Currently, there is a growing concern with the search for new sources for ethanol production, which has led to residues gaining prominence as promising raw materials. In the city of Foz do Iguaçu, located on the triple border between Brazil, Paraguay, and Argentina, the Federal Revenue Service, aiming to provide an appropriate destination for seized alcoholic beverages that need to be discarded, partnered with the Federal University of Latin American Integration to carry out their proper reuse. In this context, the objective of this work is the recovery of the ethanol contained in the seized alcoholic beverages and transferred to the University, using a Bioethanol Teaching Plant for this procedure. The methodology adopted for the execution of this work is divided into four stages: bibliographic review, mixing of alcoholic beverages (to prevent them from being resold) and transport logistics, distillation process and analysis of efficiency and yield, and forwarding of the ethanol for various uses. The results showed that, in relation to the distillation time, the flow rate of 62.5 L/h was the most viable, since under this condition, in 100 min of operation, 26.4 L of ethanol with a content of 90.5°GL were recovered, obtaining an efficiency of 62%.